2018
DOI: 10.1371/journal.pone.0201499
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum concentrations of irisin and the adipokines adiponectin and leptin with epicardial fat in cardiovascular surgery patients

Abstract: Epicardial fat located adjacent to the heart and coronary arteries is associated with increased cardiovascular risk. Irisin is a myokine produced by skeletal muscle after physical exercise, and originally described as a molecule able to promote the browning of white adipose tissue and energy expenditure. In order to decrease cardiovascular risk, it has been proposed as a promising therapeutic target in obesity and type 2 diabetes. We investigated the relationships between serum concentrations of irisin and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 58 publications
3
13
0
Order By: Relevance
“…The present study results are more or less similar to another study. 10 Studies have shown that serum leptin and hsCRP were significantly correlated in cardiac patients, and patients with CAD show higher serum leptin levels. 9 In contrast to the present results, a recent study demonstrated substantially higher serum leptin concentrations in ACS patients than control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study results are more or less similar to another study. 10 Studies have shown that serum leptin and hsCRP were significantly correlated in cardiac patients, and patients with CAD show higher serum leptin levels. 9 In contrast to the present results, a recent study demonstrated substantially higher serum leptin concentrations in ACS patients than control subjects.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 Leptin is considered a pro-inflammatory adipokine and its level is associated with the metabolic risk factors. 10 …”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the results reported by other investigators, although they did not analyze indexed values of adipocytokines. 1-6,10,11,16-18,21, [23][24][25][26][27][28][29][30][31][32][33] On the other hand, in the studies by Kim et al, 13 Kawada, 12 Macheret et al, 15 and Barnett and Piccini, 27 high circulating ADA levels were independently associated with an increased risk of AF. In addition, Ermakov et al 30 did not find any significant associations between plasma leptin and ADA concentrations and the risk of AF.…”
mentioning
confidence: 98%
“…These variations may be related to genetic factors (eg, gene polymorphism), physical activity, adipose distribution (eg, higher VAT score), sensitivity of adipocytokine receptors, and insulin resistance, the latter being an important factor leading to hyperleptinemia and a cross -talk between the adipose tissue, skeletal muscles, and liver. [1][2][3][4]9,23,32 We did not confirm the importance of adipose tissue distribution on the proarrhythmic effect of visceral obesity because the measured adipocytokines and irisin indexed to VAT were not associated with the risk of AF on admission (leptin) or were associated with a lower reduction in this risk (ADP, TNF --α, irisin) than the same parameters indexed to FM. Nonetheless, our results suggest that higher blood leptin concentrations and lower ADP and irisin levels indexed to FM and VAT may be Adipocytokines, irisin, body composition, and echocardiographic parameters We found significant correlations of blood adipocytokine and irisin concentrations, both in relation to their crude and adjusted values, with parameters of transthoracic echocardiography and body composition (data not shown).…”
mentioning
confidence: 99%
“…Decreased circulating irisin levels are associated with increased cardiovascular risk. 66,67 Recent studies demonstrated decreased irisin levels in the saliva and serum of patients with acute myocardial infarction (AMI), adding new diagnostic and prognostic information to the usual biomarkers. 60,66,68,69 Irisin has also been associated with the aging process.…”
Section: Irisin and New Associationsmentioning
confidence: 99%